Evaluación de explantes de dos variedades comerciales de clavel (Dianthus caryophyllus L.) mediante propagación in vitro utilizando dos citoquininas en cuatro dosis - Camacho Suárez , Francisco Javier (2024)
This project called: "EVALUATION OF EXPLANTS OF TWO COMMERCIAL VARIETIES OF CARNATION (Dianthus caryophyllus L.) BY IN VITRO PROPAGATION USING TWO CYTOKININS IN FOUR DOSES" has been developed in accordance with the regulations of the degree unit of the Agronomy career; current at the State University of Bolívar. The general objective that has been set in the research is to evaluate explants of two varieties of carnation; "Lege verde" (green) & "Amapola" (red), by in vitro propagation using two cytokinins; Kinetin & Benzyl adenine, in four doses; 0mg/L, 2mg/L, 4mg/L and 6mg/L. And as specific objectives, to identify which variety has a greater spread; determine the optimal dose of cytokinin that aids further spread; To assess the cost-benefit of the process of obtaining carnation explants with the optimal dose of cytokinins. The results were evaluated using Tukey's test at 5%; using a DCA design in factorial arrangement AxBxC (2x2x4xRepetitions 3), with a total of 16 treatments; obtaining by results that the best variety the "Lege verde" treatment 8 (T8), in factorial arrangement A1B2C4 (Green carnation + 6mg/L of Bencil adenine) with the best results in the variables evaluated as they were; number of shoots per explant (NBE), shoot length (LB), number of leaves per shoot (NHB), days to root emission (DER), number of roots (NR), root length (LR), and number of contaminated explants (NEC); with a benefit/cost of 1.10.